Evaluation of Virgin and Recycled LDPE Plastic Bags Manufactured using Film Blowing Machine - Kong, Pei Yee; Yong, Tze Mi; Mazlan Zakaria; Kang Chee Hwang (Progress in Engineering Application and Technology, 2022)
Plastic is a versatile material that can be shaped and molded, making it a popular choice for a wide range of items. As a result, the demand for and manufacturing plastic bags is gradually increasing. Every year, it is estimated that trillions of plastic bags are used as carrying bags all over the world. Film blowing extrusion is the most common method for producing plastic films, particularly in the packaging industry. The raw material used was Low Density Polyethylene (LDPE). Thus, in this study the mechanical properties of plastic bags are evaluated by using thickness measurement, density test, tensile test, tearing test and oxygen permeability test and make a comparison between the two companies from Wahdah Plastics Industry Sdn. Bhd. and the internet. The samples will undergo a few tests according to the American Standard Testing Method (ASTM) includes thickness measurement (ASTM D6988-13), tearing test (ASTM D689-03), tensile test (ASTM D882), oxygen permeability test (ASTM D1434-82) and density test. The results have shown that plastic sample A which is virgin LDPE from Wahdah Plastic Industries is best overall for the tensile and tearing test. In the tensile test, the most ductile sample is sample A at the cross direction. The tearing strength after divided by thickness of sample A is the highest which showed it needs more strength to tear the plastic film and withstand high tearing resistance. This sample tends to float on the water and is better for the environment since it is easy to be removed when it floats on the water. Overall, sample A which is virgin LDPE from Wahdah Plastic Industries showed the best performance in thickness, density, tensile, tearing strength and oxygen permeability test which achieved desired quality of plastic bag to sell on the market.